The health locus of control concept: Factorial structure, psychometric properties and form equivalence of the multidimensional health locus of control scales - Kassianos, Angelos P.; Symeou, Maria; Ioannou, Myria (My University, 2016)
Contradictory evidence exists on the Multidimensional Health Locus of Control scale’s factor structure and the psychometric equivalence between Form A and Form B. University students (N = 359) completed the Multidimensional Health Locus of Control and General Self-Efficacy scales. The three-factor model had better fit and parsimony in both Forms. ‘Internal’ scale negatively correlated with ‘chance’ but positively with ‘others’. The two external scales positively correlated. The scales’ reliability was satisfactory, but the two Forms were not psychometrically equivalent. Convergent validity was confirmed. The evidence suggests a three-factor structure and psychometric non-equivalence of the two Forms. Researchers should make an informed choice on which Form to use.
Keywords: Confirmatory factor analysis; Multidimensional Health Locus of Control; Reliability; Self-efficacy; Validity